Mengkaji Peran Pengembangan Pasar dalam Memperkuat Ekonomi Regional dan Distribusi Pertanian di Kota Binjai - Abdi Sugiarto (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This study aims to assess the role of market development in strengthening the regional economy and improving agricultural product distribution in Binjai City. Market development is considered a strategic instrument for enhancing economic growth, increasing farmers’ income, and ensuring efficient distribution channels between producers and consumers. This research employs a quantitative approach using primary data collected through questionnaires and interviews with traders, farmers, consumers, and local government stakeholders, complemented by secondary data from relevant institutions. Data analysis techniques include descriptive statistics and regression analysis to examine the relationship between market development, regional economic performance, and agricultural distribution efficiency. The findings indicate that market development has a positive and significant impact on regional economic strengthening, reflected in increased trade activities, job creation, and local revenue. Furthermore, improved market infrastructure and management contribute to more effective agricultural distribution by reducing transaction costs, minimizing post-harvest losses, and enhancing market accessibility. These results suggest that sustainable market development policies play a crucial role in supporting regional economic resilience and optimizing agricultural distribution systems in Binjai City.